TiAl alloy blade with gradient structure and preparation method
Through the design of gradient structure TiAl alloy blades and electron beam selection melting printing technology, the problem of mismatch in the preparation complexity and mechanical properties of low-pressure turbine blades of aero engines in the prior art is solved, and the mechanical properties matching and production of tenons and blades are achieved Improve efficiency.
Patent Information
- Application Number
- CN202411243326.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-05
AI Technical Summary
In the prior art, the method of preparing low-pressure turbine blades of aero engines is complicated, difficult to operate, and fails to effectively meet the mechanical performance requirements of different parts of the alloy blade tenon and blade body.
The gradient structure of TiAl alloy blades is designed by electron beam selection melting printing technology to prepare a gradient structure with the tenon part being equiaxed crystal and the blade body part being columnar crystal. The automatic interpolation method is used to achieve a crack-free transition interface to meet the mechanics of different parts. Performance requirements.
The mechanical properties of the tenon and the leaf body are matched, which reduces production costs and improves economic benefits. The mechanical properties and microstructure optimization of the alloy blades are improved through reasonable parameter adjustment and thermal isostatic pressure treatment.
Smart Images

Figure CN119220877A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TiAl alloy blades, and in particular to a gradient structure TiAl alloy blade and a preparation method thereof. Background Art
[0002] TiAl alloy has low density, high specific strength and excellent corrosion resistance. It is a high-temperature structural material with great potential for aircraft engines and gas turbines, with a service temperature of 600~950℃. The alloy has been used in aircraft engine turbine blades and automotive turbochargers. Currently, GE has successfully applied TiAl alloy low-pressure turbine blades to GE-nX engines and installed them on Boeing 777X aircraft. Other typical TiAl alloys such as TNM and 45XD alloys have also been installed on aircraft engines and put into service.
[0003] Electron beam additive manufacturing is a novel preparation method that converts a three-dimensional model into a two-dimensional slice, melts and solidifies metal powder into a two-dimensional slice, and repeats this process to generate a three-dimensional structure. This method has the characteristics of being able to generate complex three-dimensional structures, saving raw materials, and rapid preparation. In particular, the electron beam melting process can achieve low-stress TiAl alloy preparation, so it is widely used in the preparation process of TiAl parts. For example, the Swedish company Arcam has currently achieved mature printing of TiAl-4822 alloy blades, printing more than 60,000 blades each year.
[0004] The mechanical properties of TiAl alloy are determined by the microstructure. The room temperature microstructure of TiAl alloy includes four types of structures: near-γ, bimodal, near-lamellar, and full-lamellar. Each microstructure has different mechanical properties. For example, the room temperature plasticity of the bimodal structure is better, while the fatigue creep performance of the full-lamellar structure is better. In addition to the four types of microstructures, the grain morphology also greatly affects the mechanical properties. For example, equiaxed crystals are isotropic and suitable for multi-directional loads, while columnar crystals and single crystals have excellent mechanical properties in their growth direction and are suitable for single-directional loads.
[0005] The low-pressure turbine blades of aircraft engines are composed of a tenon and a blade body. The tenon part bears complex loads of multiple directions and types, while the blade body mainly bears the load along the blade body direction.
[0006] At present, the main methods for preparing low-pressure turbine blades for aircraft engines are additive manufacturing, ultra-high temperature forging, electrolytic manufacturing, 3D printing wax casting, welding preparation, additive manufacturing and coating composite preparation, and thermal deformation preparation.
[0007] Chinese patent CN115740494A discloses a TiAl alloy blade and a manufacturing method thereof. The method has a complex process and is difficult to operate. The setting of 3D printing process parameters is based on simulation analysis and data calculation, which deviates from the actual process. The performance of the alloy blade printed by the set process parameters cannot achieve the best effect as a whole, and the mechanical performance requirements of different parts of the alloy blade, such as the tenon and blade body, are not considered.
[0008] Chinese patent CN105821470A discloses a dual-structure TiAl alloy and a preparation method thereof, which is obtained by directional solidification of a cylindrical rod alloy using an optical floating zone crystal growth device. The main body of the alloy is columnar crystals, and endogenous γ-phase equiaxial crystals are formed at the grain boundaries of the columnar crystals. Obviously, the performance of the alloy is not suitable for aviation alloy blades, and the main performance is affected by the columnar crystal structure, and it cannot meet the mechanical performance requirements of the alloy blade tenon.
[0009] Chinese patent CN116851772A discloses a method for preparing TiAl alloy by 3D printing using a gradient strategy. This method reduces thermal stress by preparing and cutting pre-printed materials. Although it can solve the problem of large residual stress and macro cracks in the process of preparing TiAl alloy, the microstructure changes from a two-phase lamellar structure to a single-phase γ structure, and the overall performance of the prepared alloy is uniform, which is not suitable for aviation alloy blades. Summary of the invention
[0010] In order to solve the technical problems in the prior art of preparing low-pressure turbine blades for aircraft engines, such as complex processes, high operational difficulty, and failure to consider the requirements for mechanical properties of different parts of the alloy blades, such as the tenon and the blade body; the embodiment of the present invention provides a gradient structure TiAl alloy blade and preparation method that can simultaneously meet the mechanical properties of the tenon, the blade body, and the transition area between the two of the aircraft alloy blades. The technical solution is as follows:
[0011] A gradient structure TiAl alloy blade, the gradient structure TiAl alloy blade has a length of 70-300 mm, a thickness of 3-15 mm, and a chemical composition by mass percentage: Al 40-49at%, Nb 4-8at%, Mo 0.2-0.9at%, Si 0-0.2at%, B 0-0.2at%, C 0-0.2at%, and the remainder is Ti and unavoidable inclusions; wherein the lower limit values of Si and B of the aforementioned elements cannot be 0.
[0012] Optionally, the tenon portion of the gradient structure TiAl alloy blade is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystal, and the columnar crystal part is α2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0013] Optionally, the room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade are: tensile strength of 600-700MPa, yield strength of 500-600MPa, yield strength ratio of 0.823-0.929, elongation of 2-3%, and fatigue limit of 500-600MPa; the room temperature mechanical properties of the blade body part are: tensile strength of 700-900MPa, yield strength of 600-800MPa, yield strength ratio of 0.821-0.900, elongation of 0.5-1.5%, and fatigue limit of 500-700MPa.
[0014] A method for preparing a gradient structure TiAl alloy blade is provided. The method for preparing a gradient structure TiAl alloy blade comprises the following steps:
[0015] S1. Melting: weighing and mixing pure metal Ti and Al with a purity of 99.9% and master alloys Al-Nb, Al-Mo and Al-Si as raw materials according to the composition ratio, using vacuum induction suspension melting to obtain alloy melt, and casting to obtain ingots;
[0016] S2, casting: casting the ingot of S1 of required mass by a centrifugal casting machine to obtain an electrode rod;
[0017] S3, surface treatment and processing: remove the surface oxide scale of the electrode rod of S2, and then round off the corners to obtain an electrode rod suitable for the rotating electrode method;
[0018] S4, alloy powder preparation: the electrode rod of S3 is used to prepare alloy powder by a rotating electrode method to obtain alloy powder for 3D printing;
[0019] S5, alloy powder processing: sieving and packaging the alloy powder for 3D printing in S4 to obtain finished alloy powder for 3D printing with a powder particle size controlled at 45-150 μm and an oxygen content controlled at less than 500 ppm;
[0020] S6, electron beam selective melting: The finished alloy powder for 3D printing in S5 is subjected to electron beam selective melting printing to prepare a gradient structure TiAl alloy blade.
[0021] Optionally, the vacuum degree of vacuum induction levitation melting in S1 is controlled at 5×10 -3 -1×10 -4 Pa, the smelting times are controlled at 3-5 times, and the size of the ingot is Φ40×400mm-Φ80×700mm.
[0022] Optionally, the ingot of S1 is placed in a centrifugal casting machine after removing the surface oxide scale.
[0023] Optionally, during the centrifugal casting process in S2, asbestos is wrapped outside the casting mold to prevent cracks caused by rapid cooling, and the diameter of the electrode rod is 40-75 mm.
[0024] Optionally, after the centrifugal casting in S2 is completed, the furnace temperature is lowered to 200° C. and the mold is taken out of the furnace. When the mold shell temperature is lowered to below 100° C., the ceramic mold shell is removed by sandblasting, and the electrode rod is cut off by wire cutting.
[0025] Optionally, in S3, the electrode rod blank is turned to remove oxide scale, the surface roughness Ra=0.4-3.2μm, and the fillet radius size is R1-5mm.
[0026] Optionally, when the rotating electrode is used to prepare the alloy powder in S4, the protective atmosphere is high-purity argon gas, and when the alloy powder is packaged in S5, the container needs to be filled with argon gas and then sealed.
[0027] Optionally, the fluidity of the alloy powder for 3D printing in S4 should be less than 30s / 50g, the hollow powder rate should be less than 0.1%, and the bulk density should be greater than 2.4g / cm 3 , tap density greater than 2.5g / cm 3 .
[0028] Optionally, in S6, the finished alloy powder for 3D printing in S5 needs to be screened once using a PRS device before electron beam selective melting printing.
[0029] Optionally, powder needs to be spread before electron beam selective melting printing in S6. A layer thickness of 50-100 μm is selected during the powder spreading process. The target temperature of the powder bed sintering process during electron beam selective melting reaches 1170-1190°C, and the temperature tries to reach the Tα value within the working range of the machine.
[0030] Optionally, the base plate needs to be preheated before the electron beam selective melting printing and powder laying in S6, and the preheating temperature reaches 1200-1220°C and the preheating time is 30-50 minutes.
[0031] Optionally, the preheating in S6 adopts 5+5+10 electron beam scanning, the current gradually increases from 12 to 20 in the first 5 times, increases from 20 to 40 in the middle 5 times, and increases from 40 to 60 in the last 10 times.
[0032] Optionally, in S6, the partial melting parameters of the lower equiaxed crystal in the electron beam selective melting printing use a current of 8-8.5 mA, a scanning speed of 1.9-2.1 m / s, a scanning path set to a random scattered point scanning mode, and a defocus value of 30-50.
[0033] Optionally, in the electron beam selective melting printing in S6, the melting parameters of the upper columnar crystal part use a current of 7.5-8 mA, a scanning speed of 1.8-2.0 m / s, a scanning path set to line-scan mode, and a defocus value of 30-35.
[0034] Optionally, in S6, the melting parameters of the transition zone in the electron beam selective melting printing use an automatic interpolation method, and when a layer thickness of 50 μm is used, the transition layer is not less than 10 layers, and when a layer thickness of 70 μm is used, the transition layer is not less than 8 layers.
[0035] Optionally, in the electron beam selective melting printing in S6, the post-preheating parameters use an average beam current of 12 mA and perform 15 scans.
[0036] Optionally, after the electron beam selective melting printing in S6 is completed, the printed product needs to be subjected to hot isostatic pressing treatment, and the process parameters of the temperature should not be higher than 1240° C. and the pressure should be higher than 200 MPa.
[0037] Optionally, after hot isostatic pressing is completed, the printed product needs to be heat treated, and the heat treatment parameter temperature should not be higher than 1275°C, and the time should not be higher than 10 minutes.
[0038] Optionally, a CT analysis is performed on the alloy blade after the heat treatment, and no holes should be found at a scanning accuracy of 30 μm.
[0039] Optionally, the prepared gradient structure TiAl alloy blade is subjected to anatomical analysis, and the tenon portion should be entirely equiaxed crystals, and the blade body portion should be entirely columnar crystals.
[0040] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0041] The above scheme, the present invention proposes a gradient structure TiAl alloy blade and a preparation method, which can solve many technical problems existing in the preparation process of TiAl alloy blades, thereby reducing production costs and improving economic benefits.
[0042] The present invention prepares alloy powder through the preparation and reasonable parameter adjustment, utilizes the relationship between energy input-electron beam morphology-crystal growth, uses electron beam selective melting of alloy powder to prepare, realizes the gradient structure of lower equiaxed crystal-upper columnar crystal by controlling the energy input density and electron beam morphology, realizes the crack-free transition interface in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method; the structure can utilize the unique mechanical properties of different microstructures to match the service requirements of different parts of the blade, and proposes a new concept for the material-function integration of 3D printed TiAl blades.
[0043] The preparation of the alloy powder of the present invention requires controllable composition design, and the electrode rod is obtained by two castings. The electrode rod can only be obtained by the rotating electrode method. The prepared alloy powder for electron beam selective melting should have a fluidity of less than 30s / 50g, a hollow powder rate of less than 0.1%, and a loose density of more than 2.4g / cm 3 , tap density greater than 2.5g / cm 3 .
[0044] The base plate needs to be preheated before the powder is spread by electron beam selective melting printing of the present invention. The preheating adopts 5+5+10 electron beam scannings. The current is gradually increased from 12 to 20 in the first 5 times, from 20 to 40 in the middle 5 times, and from 40 to 60 in the last 10 times, so that the base plate is preheated to a sufficient temperature without deformation.
[0045] Reasonable parameter adjustment of the present invention includes current, scanning speed, and defocus value, so that two different microstructures can be printed on a blade without increasing printing steps and links, thereby realizing structural and functional integration.
[0046] The hot isostatic pressing treatment of the present invention can eliminate defects occurring during the printing process of the prepared TiAl alloy blade and effectively improve the mechanical properties.
[0047] The heat treatment after hot isostatic pressing of the present invention can enable the prepared TiAl alloy blade to obtain an optimized microstructure with the characteristics of fine full lamellar layers.
[0048] The tenon of the gradient structure TiAl alloy blade prepared by the present invention is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystal, and the columnar crystal part is α 2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0049] The room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade prepared by the present invention are as follows: tensile strength of 600-700 MPa, yield strength of 500-600 MPa, yield strength ratio of 0.823-0.929, elongation of 2-3%, and fatigue limit of 500-600 MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength of 700-900 MPa, yield strength of 600-800 MPa, yield strength ratio of 0.821-0.900, elongation of 0.5-1.5%, and fatigue limit of 500-700 MPa.
[0050] In summary, compared with other traditional methods, the method of the present invention prepares and adjusts the tenon and blade body of the blade with different organizational structures through the selection and preparation of the composition of the alloy powder and the regulation of the electron beam selective melting process steps; it can simultaneously meet the room temperature and high temperature performance requirements of the tenon and blade body of aviation alloy blades, has high resource utilization, short process, high efficiency, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0052] Figure 1 is an equiaxed grain microstructure diagram of the gradient structure TiAl alloy blade of Example 1 of the present invention;
[0053] Figure 2 is a columnar crystal microstructure diagram of the gradient structure TiAl alloy blade of Example 1 of the present invention;
[0054] Figure 3 is an equiaxed grain microstructure diagram of a gradient structure TiAl alloy blade according to Example 2 of the present invention;
[0055] Figure 4 is a columnar crystal microstructure diagram of a gradient structure TiAl alloy blade according to Example 2 of the present invention;
[0056] Figure 5 Schematic diagram of a low-pressure turbine blade of a gradient-structured TiAl alloy blade according to Example 3 of the present invention;
[0057] Figure 6 This is a printed physical image of a gradient TiAl alloy low-pressure turbine blade of a gradient structure TiAl alloy blade of Example 3 of the present invention;
[0058] Figure 7 This is a printed CT inspection image of a gradient TiAl alloy low-pressure turbine blade of a gradient structure TiAl alloy blade according to Example 3 of the present invention;
[0059] Figure 8 This is an anatomical analysis diagram of a gradient TiAl alloy low-pressure turbine blade of a gradient structure TiAl alloy blade of Example 3 of the present invention. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0061] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0062] In the embodiments of the present invention, "image" and "picture" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they want to express are the same. "of", "corresponding" and "corresponding" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they want to express are the same.
[0063] In the embodiments of the present invention, sometimes the subscripts such as W 1 It may be written in non-subscript form such as W1. When the difference is not emphasized, the meaning is the same.
[0064] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0065] A gradient structure TiAl alloy blade, the gradient structure TiAl alloy blade has a length of 70-300 mm, a thickness of 3-15 mm, and a chemical composition by mass percentage: Al 40-49at%, Nb 4-8at%, Mo 0.2-0.9at%, Si 0-0.2at%, B 0-0.2at%, C 0-0.2at%, and the remainder is Ti and unavoidable inclusions; wherein the lower limit values of Si and B of the aforementioned elements cannot be 0.
[0066] In particular, the tenon portion of the gradient structure TiAl alloy blade is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystal, and the columnar crystal part is α 2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0067] In particular, the room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade are as follows: tensile strength of 600-700MPa, yield strength of 500-600MPa, yield strength ratio of 0.823-0.929, elongation of 2-3%, and fatigue limit of 500-600MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength of 700-900MPa, yield strength of 600-800MPa, yield strength ratio of 0.821-0.900, elongation of 0.5-1.5%, and fatigue limit of 500-700MPa.
[0068] A method for preparing a gradient structure TiAl alloy blade is provided. The method for preparing a gradient structure TiAl alloy blade comprises the following steps:
[0069] S1. Melting: weighing and mixing pure metal Ti and Al with a purity of 99.9% and master alloys Al-Nb, Al-Mo and Al-Si as raw materials according to the composition ratio, using vacuum induction suspension melting to obtain alloy melt, and casting to obtain ingots;
[0070] S2, casting: casting the ingot of S1 of required mass by a centrifugal casting machine to obtain an electrode rod;
[0071] S3, surface treatment and processing: remove the surface oxide scale of the electrode rod of S2, and then round off the corners to obtain an electrode rod suitable for the rotating electrode method;
[0072] S4, alloy powder preparation: the electrode rod of S3 is used to prepare alloy powder by a rotating electrode method to obtain alloy powder for 3D printing;
[0073] S5, alloy powder processing: sieving and packaging the alloy powder for 3D printing in S4 to obtain finished alloy powder for 3D printing with a powder particle size controlled at 45-150 μm and an oxygen content controlled at less than 500 ppm;
[0074] S6, electron beam selective melting: The finished alloy powder for 3D printing in S5 is subjected to electron beam selective melting printing to prepare a gradient structure TiAl alloy blade.
[0075] In particular, the vacuum degree of vacuum induction levitation melting in S1 is controlled at 5×10 -3 -1×10 -4 Pa, the smelting times are controlled at 3-5 times, and the size of the ingot is Φ40×400mm-Φ80×700mm.
[0076] Specifically, the ingot of S1 is placed in a centrifugal casting machine after removing the surface oxide scale.
[0077] In particular, during the centrifugal casting process in S2, asbestos was wrapped outside the casting mold to prevent cracks caused by rapid cooling, and the diameter of the electrode rod was 40-75 mm.
[0078] In particular, after the centrifugal casting in S2 is completed, the temperature in the furnace is lowered to 200°C and the mold is taken out of the furnace. When the shell temperature is lowered to below 100°C, the ceramic shell is removed by sandblasting, and the electrode rod is cut off by wire cutting.
[0079] In particular, the electrode rod blank in S3 is turned to remove oxide scale, with a surface roughness of Ra = 0.4-3.2 μm and a fillet radius size of R1-5 mm.
[0080] In particular, when the rotating electrode is used to prepare the alloy powder in S4, the protective atmosphere is high-purity argon gas, and when the alloy powder is packaged in S5, the container needs to be filled with argon gas and then sealed.
[0081] In particular, the fluidity of alloy powder for 3D printing in S4 should be less than 30s / 50g, the hollow powder rate should be less than 0.1%, and the bulk density should be greater than 2.4g / cm 3 , tap density greater than 2.5g / cm 3 .
[0082] In particular, in S6, the finished alloy powder for 3D printing in S5 needs to be screened once using the PRS device before electron beam selective melting printing.
[0083] In particular, powder needs to be spread before electron beam selective melting printing in S6. During the powder spreading process, a layer thickness of 50-100μm is selected. During the electron beam selective melting process, the target temperature of the powder bed sintering process reaches 1170-1190℃, and the temperature tries to reach the Tα value within the working range of the machine.
[0084] In particular, the base plate needs to be preheated before powder coating in electron beam selective melting printing in S6, with the preheating temperature reaching 1200-1220°C and the preheating time being 30-50 minutes.
[0085] In particular, the preheating in S6 adopts 5+5+10 electron beam scans, the current gradually increases from 12 to 20 in the first 5 passes, increases from 20 to 40 in the middle 5 passes, and increases from 40 to 60 in the last 10 passes.
[0086] In particular, the partial melting parameters of the lower equiaxed crystal in the electron beam selective melting printing in S6 use a current of 8-8.5 mA, a scanning speed of 1.9-2.1 m / s, a scanning path set to a random scattered point scanning mode, and a defocus value of 30-50.
[0087] In particular, the melting parameters of the upper columnar crystal part in the electron beam selective melting printing in S6 use a current of 7.5-8mA, a scanning speed of 1.8-2.0m / s, a scanning path set to line-scan mode, and a defocus value of 30-35.
[0088] In particular, the melting parameters of the transition zone in the electron beam selective melting printing in S6 use the automatic interpolation method, and the transition layer is not less than 10 layers when the layer thickness is 50 μm, and the transition layer is not less than 8 layers when the layer thickness is 70 μm.
[0089] In particular, the post-preheating parameters in the electron beam selective melting printing in S6 used an average beam current of 12 mA and performed 15 scans.
[0090] In particular, after the electron beam selective melting printing in S6 is completed, the printed product needs to be subjected to hot isostatic pressing. The process parameters of the temperature should not be higher than 1240°C and the pressure should be higher than 200MPa.
[0091] In particular, after hot isostatic pressing is completed, the printed product needs to be heat treated, and the heat treatment parameter temperature should not be higher than 1275°C and the time should not be higher than 10 minutes.
[0092] In particular, CT analysis of the alloy blade after heat treatment should show no holes at a scanning accuracy of 30μm.
[0093] In particular, the prepared gradient structure TiAl alloy blade is anatomically analyzed, and the tenon part should be entirely equiaxed crystals, and the blade body part should be entirely columnar crystals.
[0094] Example 1
[0095] The present embodiment is a gradient structure TiAl alloy blade, the length of the gradient structure TiAl alloy blade is 70 mm, the thickness is 4 mm, and the chemical composition is as follows by mass percentage: Al 44at%, Nb 4at%, Mo 0.5at%, Si 0.2at%, B 0.05at%, and the remainder is Ti and unavoidable inclusions.
[0096] A method for preparing the gradient structure TiAl alloy blades as described above comprises the following steps:
[0097] S1. Melting: Pure metal Ti and Al with a purity of 99.9% and intermediate alloys Al-Nb, Al-Mo, and Al-Si are weighed and mixed according to the composition ratio as raw materials, and alloy melt is obtained by vacuum induction levitation melting. The vacuum degree of vacuum induction levitation melting is controlled at 5×10 -3 Pa, the number of smelting times is controlled at 3 times, and the ingot with the size of Φ60×400mm is cast;
[0098] S2, casting: after removing the surface oxide scale of the ingot of S1 of the required quality, put it into a centrifugal casting machine, and cast it by the centrifugal casting machine. During the centrifugal casting process, asbestos is wrapped outside the casting mold to prevent cracks caused by rapid cooling. After the centrifugal casting is completed, the furnace temperature is lowered to 200°C and the mold is taken out of the furnace. When the shell temperature is lowered to below 100°C, the ceramic shell is removed by sandblasting, and the electrode rod is cut by wire cutting to obtain an electrode rod with a diameter of 50 mm;
[0099] S3, surface treatment and processing: remove the surface oxide scale and chamfer the electrode rod of S2, the surface roughness Ra = 2μm, the chamfer radius size is R1.5mm, and then chamfer the corners to obtain an electrode rod with a diameter of 45mm suitable for the rotating electrode method;
[0100] S4, alloy powder preparation: the electrode rod of S3 is used to prepare alloy powder by a rotating electrode method, and the protective atmosphere used in the rotating electrode preparation of the alloy powder is high-purity argon gas, to obtain alloy powder for 3D printing, the particle size of the alloy powder for 3D printing is 45-140 μm, and the oxygen content is 400 ppm;
[0101] S5. Alloy powder processing: The alloy powder for 3D printing of S4 is screened and packaged. When packaging the alloy powder, the container needs to be filled with argon and then sealed to obtain a finished alloy powder for 3D printing with a powder particle size of 45-150μm and an oxygen content of less than 500ppm; the fluidity of the alloy powder for 3D printing should be less than 30s / 50g, the hollow powder rate should be less than 0.1%, and the bulk density should be greater than 2.4g / cm 3 , tap density greater than 2.5g / cm 3 ;
[0102] S6, electron beam selective melting: Before the finished alloy powder for 3D printing of S5 is subjected to electron beam selective melting printing, it is necessary to use a PRS device to screen it once, and then the screened finished alloy powder for 3D printing is spread to perform electron beam selective melting printing. During the powder spreading process, a layer thickness of 50 μm is selected. During the electron beam selective melting process, the target temperature of the powder bed sintering process reaches 1170-1190°C, and the temperature reaches the Tα value as much as possible within the working range of the machine to prepare a gradient structure TiAl alloy blade;
[0103] In S6, the base plate needs to be preheated before powder coating in electron beam selective melting printing, and the preheating temperature reaches 1200℃ and the preheating time is 30min; the preheating adopts 5+5+10 electron beam scanning, and the current gradually increases from 12 to 20 in the first 5 times, from 20 to 40 in the middle 5 times, and from 40 to 60 in the last 10 times; the current used for the melting parameters of the lower equiaxed crystal part in electron beam selective melting printing is 8mA, the scanning path selects the random point melting mode, the scanning speed is 2.0m / s, and the defocus value is 45; the current used for the melting parameters of the upper columnar crystal part in electron beam selective melting printing is 7.5mA, the scanning speed is 1.8m / s, and the defocus value is 30; the melting parameters of the transition zone in electron beam selective melting printing use the automatic interpolation method, and the transition layer is not less than 10 layers when the layer thickness is 50μm, and the transition layer is not less than 8 layers when the layer thickness is 70μm.
[0104] In this embodiment, the gradient structure TiAl alloy blade prepared is anatomically analyzed. The tenon part should be entirely equiaxed crystals, and the blade body part should be entirely columnar crystals.
[0105] The tenon head of the gradient structure TiAl alloy blade prepared in this embodiment is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystal, and the columnar crystal part is α 2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0106] The equiaxed crystal microstructure of the sample printed in this embodiment was observed using a scanning electron microscope, as shown in the following figure: Figure 1 The picture shown shows that the grain size is about 10 μm and the microstructure consists of α 2 The equiaxed crystal microstructure was observed by scanning electron microscope, and the following results were obtained: Figure 2 Pictures shown.
[0107] The average grain size of the equiaxed crystals in the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment is 8 μm, and the average grain size of the columnar crystals in the blade body part is 30 μm.
[0108] The room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment are as follows: tensile strength of 650 MPa, yield strength of 550 MPa, yield strength ratio of 0.846, elongation of 2%, strength-plastic product of 1.30 GPa·%, and fatigue limit of 500 MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength of 750 MPa, yield strength of 650 MPa, yield strength ratio of 0.867, elongation of 1%, strength-plastic product of 0.75 GPa·%, and fatigue limit of 550 MPa.
[0109] Example 2
[0110] The present embodiment is a gradient structure TiAl alloy blade, the length of the gradient structure TiAl alloy blade is 120 mm, the thickness is 5 mm, and the chemical composition is as follows by mass percentage: Al 44at%, Nb 4at%, Mo 0.5at%, Si0.2at%, B 0.1at%, C 0.05at%, and the remainder is Ti and unavoidable inclusions.
[0111] A method for preparing the gradient structure TiAl alloy blades as described above comprises the following steps:
[0112] S1. Melting: Pure metal Ti and Al with a purity of 99.9% and intermediate alloys Al-Nb, Al-Mo, and Al-Si are weighed and mixed according to the composition ratio as raw materials, and alloy melt is obtained by vacuum induction levitation melting. The vacuum degree of vacuum induction levitation melting is controlled at 3×10 -4 Pa, the number of smelting times is controlled at 3 times, and the ingot with the size of Φ55×500mm is cast;
[0113] S2, casting: after removing the surface oxide scale of the ingot of S1 of the required mass, put it into a centrifugal casting machine, and cast it by the centrifugal casting machine. During the centrifugal casting process, asbestos is wrapped outside the casting mold to prevent cracks caused by rapid cooling. After the centrifugal casting is completed, the furnace temperature is lowered to 200°C and the mold is taken out of the furnace. When the shell temperature is lowered to below 100°C, the ceramic shell is removed by sandblasting, and the electrode rod is cut by wire cutting to obtain an electrode rod with a diameter of 58 mm;
[0114] S3, surface treatment and processing: remove the surface oxide scale and chamfer the electrode rod of S2, the surface roughness Ra = 2.6μm, the chamfer radius size is R3.2mm, and then chamfer the corners to obtain an electrode rod with a diameter of 52mm suitable for the rotating electrode method;
[0115] S4, alloy powder preparation: the electrode rod of S3 is used to prepare alloy powder by a rotating electrode method, and the protective atmosphere is high-purity argon gas when the rotating electrode is used to prepare the alloy powder, so as to obtain alloy powder for 3D printing, and the particle size of the alloy powder for 3D printing is 40-120 μm and the oxygen content is 460 ppm;
[0116] S5. Alloy powder processing: The alloy powder for 3D printing of S4 is screened and packaged. When packaging the alloy powder, the container needs to be filled with argon and then sealed to obtain a finished alloy powder for 3D printing with a powder particle size of 45-150μm and an oxygen content of less than 500ppm; the fluidity of the alloy powder for 3D printing should be less than 30s / 50g, the hollow powder rate should be less than 0.1%, and the bulk density should be greater than 2.4g / cm 3, tap density greater than 2.5g / cm 3 ;
[0117] S6, electron beam selective melting: Before the finished alloy powder for 3D printing of S5 is subjected to electron beam selective melting printing, it is necessary to use a PRS device to screen it once, and then the screened finished alloy powder for 3D printing is spread on the powder for electron beam selective melting printing. During the powder spreading process, a layer thickness of 70 μm is selected. During the electron beam selective melting process, the target temperature of the powder bed sintering process reaches 1190°C, and the temperature reaches the Tα value as much as possible within the working range of the machine to prepare a gradient structure TiAl alloy blade;
[0118] In S6, the base plate needs to be preheated before powdering in electron beam selective melting printing, and the preheating temperature reaches 1200℃ and the preheating time is 35min. The preheating adopts 5+5+10 electron beam scanning, and the current gradually increases from 12 to 20 in the first 5 times, from 20 to 40 in the middle 5 times, and from 40 to 60 in the last 10 times. The current used for the melting parameters of the lower equiaxed crystal part in electron beam selective melting printing is 8.5mA, the scanning speed is 2.1m / s, and the defocus value is 50; the current used for the melting parameters of the upper columnar crystal part in electron beam selective melting printing is 7.5mA, the scanning speed is 1.8m / s, and the defocus value is 35; the melting parameters of the transition zone in electron beam selective melting printing use the automatic interpolation method, and the transition layer is not less than 8 layers when the layer thickness is 70μm, which is 10 layers;
[0119] In this embodiment, the gradient structure TiAl alloy blade prepared is anatomically analyzed. The tenon part should be entirely equiaxed crystals, and the blade body part should be entirely columnar crystals.
[0120] The tenon head of the gradient structure TiAl alloy blade prepared in this embodiment is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystal, and the columnar crystal part is α 2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0121] The equiaxed crystal microstructure of the sample printed in this embodiment was observed using a scanning electron microscope, as shown in the following figure: Figure 3 The picture shown shows that the grain size is about 10 μm and the microstructure consists of α 2 The equiaxed crystal microstructure was observed by scanning electron microscope, and the following results were obtained: Figure 4 Pictures shown.
[0122] The average grain size of the equiaxed crystals in the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment is 10 μm, and the average grain size of the columnar crystals in the blade body part is 35 μm.
[0123] The room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment are as follows: tensile strength is 620MPa, yield strength is 510MPa, yield strength ratio is 0.823, elongation is 1.8%, strength-plastic product is 1.12GPa·%, and fatigue limit is 470MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength is 800MPa, yield strength is 720MPa, yield strength ratio is 0.900, elongation is 1.2%, strength-plastic product is 0.96GPa·%, and fatigue limit is 650MPa.
[0124] Example 3
[0125] The present embodiment is a gradient structure TiAl alloy blade, the length of the gradient structure TiAl alloy blade is 180 mm, the thickness is 6 mm, and the chemical composition is as follows by mass percentage: Al 44at%, Nb 4at%, Mo 0.5at%, Si0.2at%, B 0.1at%, and the remainder is Ti and unavoidable inclusions.
[0126] A method for preparing the gradient structure TiAl alloy blades as described above comprises the following steps:
[0127] S1. Melting: Pure metal Ti and Al with a purity of 99.9% and intermediate alloys Al-Nb, Al-Mo, and Al-Si are weighed and mixed according to the composition ratio as raw materials, and alloy melt is obtained by vacuum induction levitation melting. The vacuum degree of vacuum induction levitation melting is controlled at 2×10 -3 Pa, the number of smelting times is controlled at 3 times, and the ingot with the size of Φ80×700mm is cast;
[0128] S2, casting: after removing the surface oxide scale of the ingot of S1 of the required mass, put it into a centrifugal casting machine, and cast it by the centrifugal casting machine. During the centrifugal casting process, asbestos is wrapped outside the casting mold to prevent cracks caused by rapid cooling. After the centrifugal casting is completed, the furnace temperature is lowered to 200°C and the mold is taken out of the furnace. When the shell temperature is lowered to below 100°C, the ceramic shell is removed by sandblasting, and the electrode rod is cut by wire cutting to obtain an electrode rod with a diameter of 75 mm;
[0129] S3, surface treatment and processing: remove the surface oxide scale and chamfer the electrode rod of S2, the surface roughness Ra = 3.0μm, the chamfer radius size is R2.5mm, and then chamfer the corners to obtain an electrode rod with a diameter of 70mm suitable for the rotating electrode method;
[0130] S4, alloy powder preparation: the electrode rod of S3 is used to prepare alloy powder by a rotating electrode method, and the protective atmosphere is high-purity argon gas when the rotating electrode is used to prepare the alloy powder, so as to obtain alloy powder for 3D printing, and the particle size of the alloy powder for 3D printing is 40-130 μm and the oxygen content is 440 ppm;
[0131] S5. Alloy powder processing: The alloy powder for 3D printing of S4 is screened and packaged. When packaging the alloy powder, the container needs to be filled with argon and then sealed to obtain a finished alloy powder for 3D printing with a powder particle size of 45-150μm and an oxygen content of less than 500ppm; the fluidity of the alloy powder for 3D printing should be less than 30s / 50g, the hollow powder rate should be less than 0.1%, and the bulk density should be greater than 2.4g / cm 3 , tap density greater than 2.5g / cm 3 ;
[0132] S6, electron beam selective melting: Before the finished alloy powder for 3D printing of S5 is subjected to electron beam selective melting printing, it is necessary to use a PRS device to screen it once, and then the screened finished alloy powder for 3D printing is spread on the powder for electron beam selective melting printing. A layer thickness of 50 μm is selected during the powder spreading process. During the electron beam selective melting process, the target temperature of the powder bed sintering process reaches 1170°C, and the temperature reaches the Tα value as much as possible within the working range of the machine to prepare a gradient structure TiAl alloy blade;
[0133] In S6, the base plate needs to be preheated before powdering in electron beam selective melting printing, and the preheating temperature reaches 1200℃ and the preheating time is 30min. The preheating adopts 5+5+10 electron beam scanning, and the current gradually increases from 12 to 20 in the first 5 times, from 20 to 40 in the middle 5 times, and from 40 to 60 in the last 10 times. The current used for the melting parameters of the lower equiaxed crystal part in the electron beam selective melting printing is 8.3mA, the scanning path selects the random point melting mode, the scanning speed is 1.9m / s, and the defocus value is 48; the current used for the melting parameters of the upper columnar crystal part in the electron beam selective melting printing is 7.8mA, the scanning path selects the line-scan mode, the scanning speed is 1.9m / s, and the defocus value is 32; the transition zone melting parameters in the electron beam selective melting printing use the automatic interpolation method, and the transition layer is not less than 10 layers when the layer thickness is 50μm, which is 12 layers; among them, using Figure 5 The blade model shown in the figure is printed, and the equiaxed crystal-columnar crystal gradient structure printing method is used to obtain the following Figure 6 Actual blade shown.
[0134] After the electron beam selective melting printing in S6 is completed, the printed product needs to be subjected to hot isostatic pressing. The process parameters are temperature of 1235°C and pressure of 200MPa. After the hot isostatic pressing is completed, the printed product needs to be heat treated. The heat treatment parameters are temperature of 1260°C and time of 10 minutes.
[0135] In this example, the prepared gradient structure TiAl alloy blade was subjected to CT analysis, and the scanning accuracy was 30 μm. Figure 7 The leaves were dissected as shown. Figure 8 The tenon part should be all equiaxed crystals, and the blade part should be all columnar crystals.
[0136] The tenon head of the gradient structure TiAl alloy blade prepared in this embodiment is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystal, and the columnar crystal part is α 2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0137] The average grain size of the equiaxed crystals in the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment is 12 μm, and the average grain size of the columnar crystals in the blade body part is 45 μm.
[0138] The room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment are as follows: tensile strength of 620 MPa, yield strength of 510 MPa, yield strength ratio of 0.823, elongation of 2.3%, strength-plastic product of 1.43 GPa·%, and fatigue limit of 540 MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength of 850 MPa, yield strength of 750 MPa, yield strength ratio of 0.882, elongation of 1.7%, strength-plastic product of 1.45 GPa·%, and fatigue limit of 650 MPa.
[0139] Example 4
[0140] The present embodiment is a gradient structure TiAl alloy blade, the length of the gradient structure TiAl alloy blade is 200 mm, the thickness is 6 mm, and the chemical composition is as follows by mass percentage: Al 45at%, Nb 4at%, Mo 0.6at%, Si0.1at%, B 0.05at%, C 0.05at%, and the remainder is Ti and unavoidable inclusions.
[0141] A method for preparing the gradient structure TiAl alloy blades as described above comprises the following steps:
[0142] S1. Melting: Pure metal Ti and Al with a purity of 99.9% and intermediate alloys Al-Nb, Al-Mo, and Al-Si are weighed and mixed according to the composition ratio as raw materials, and alloy melt is obtained by vacuum induction levitation melting. The vacuum degree of vacuum induction levitation melting is controlled at 1.5×10 -3 Pa, the number of smelting times is controlled at 3 times, and the ingot with the size of Φ70×600mm is cast;
[0143] S2, casting: after removing the surface oxide scale of the ingot of S1 of the required mass, put it into a centrifugal casting machine, and cast it by the centrifugal casting machine. During the centrifugal casting process, asbestos is wrapped outside the casting mold to prevent cracks caused by rapid cooling. After the centrifugal casting is completed, the furnace temperature is lowered to 200°C and the mold is taken out of the furnace. When the shell temperature is lowered to below 100°C, the ceramic shell is removed by sandblasting, and the electrode rod is cut by wire cutting to obtain an electrode rod with a diameter of 55 mm;
[0144] S3, surface treatment and processing: remove the surface oxide scale and chamfer the electrode rod of S2, the surface roughness Ra = 1.8μm, the chamfer radius size is R2.2mm, and then chamfer the corners to obtain an electrode rod with a diameter of 50mm suitable for the rotating electrode method;
[0145] S4, alloy powder preparation: the electrode rod of S3 is used to prepare alloy powder by a rotating electrode method, and the protective atmosphere used in the rotating electrode preparation of the alloy powder is high-purity argon gas, to obtain alloy powder for 3D printing, the particle size of the alloy powder for 3D printing is 60-130 μm, and the oxygen content is 330 ppm;
[0146] S5. Alloy powder processing: The alloy powder for 3D printing of S4 is screened and packaged. When packaging the alloy powder, the container needs to be filled with argon and then sealed to obtain a finished alloy powder for 3D printing with a powder particle size of 45-150μm and an oxygen content of less than 500ppm; the fluidity of the alloy powder for 3D printing should be less than 30s / 50g, the hollow powder rate should be less than 0.1%, and the bulk density should be greater than 2.4g / cm 3 , tap density greater than 2.5g / cm 3 ;
[0147] S6, electron beam selective melting: Before the finished alloy powder for 3D printing of S5 is subjected to electron beam selective melting printing, it is necessary to use a PRS device to screen it once, and then the screened finished alloy powder for 3D printing is spread on the powder for electron beam selective melting printing. A layer thickness of 100 μm is selected during the powder spreading process. During the electron beam selective melting process, the target temperature of the powder bed sintering process reaches 1190°C, and the temperature reaches the Tα value as much as possible within the working range of the machine to prepare a gradient structure TiAl alloy blade;
[0148] In S6, the base plate needs to be preheated before powder coating in electron beam selective melting printing, and the preheating temperature reaches 1220℃ and the preheating time is 50min; the preheating adopts 5+5+10 electron beam scanning, and the current gradually increases from 12 to 20 in the first 5 times, from 20 to 40 in the middle 5 times, and from 40 to 60 in the last 10 times; the melting parameters of the lower equiaxed crystal part in electron beam selective melting printing use a current of 8.2mA, a scanning speed of 2.0m / s, a random point melting strategy is used for the scanning path, and the defocus value is 40; the melting parameters of the upper columnar crystal part in electron beam selective melting printing use a current of 8mA, a scanning speed of 1.9m / s, a line-scan strategy is used for the scanning path, and the defocus value is 32; the melting parameters of the transition zone in electron beam selective melting printing use the automatic interpolation method, and the transition layer is not less than 10 layers when the layer thickness is 50μm, and the transition layer is not less than 8 layers when the layer thickness is 70μm.
[0149] In this embodiment, the gradient structure TiAl alloy blade prepared is anatomically analyzed. The tenon part should be entirely equiaxed crystals, and the blade body part should be entirely columnar crystals.
[0150] The tenon head of the gradient structure TiAl alloy blade prepared in this embodiment is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade and the preparation method is columnar crystal, and the columnar crystal part is α 2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0151] The average grain size of the equiaxed crystals in the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment is 11 μm, and the average grain size of the columnar crystals in the blade body part is 44 μm.
[0152] The room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment are as follows: tensile strength of 700 MPa, yield strength of 650 MPa, yield strength ratio of 0.929, elongation of 2%, strength-plastic product of 1.40 GPa·%, and fatigue limit of 600 MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength of 950 MPa, yield strength of 850 MPa, yield strength ratio of 0.895, elongation of 1.3%, strength-plastic product of 1.24 GPa·%, and fatigue limit of 800 MPa.
[0153] Example 5
[0154] The present embodiment is a gradient structure TiAl alloy blade, the length of the gradient structure TiAl alloy blade is 260 mm, the thickness is 8 mm, and the chemical composition is as follows by mass percentage: Al 46at%, Nb 5at%, Mo 0.5at%, Si 0at%, B0.15at%, C 0.15%, and the remainder is Ti and unavoidable inclusions.
[0155] A method for preparing the gradient structure TiAl alloy blades as described above comprises the following steps:
[0156] S1. Melting: Pure metal Ti and Al with a purity of 99.9% and intermediate alloys Al-Nb, Al-Mo, and Al-Si are weighed and mixed according to the composition ratio as raw materials, and alloy melt is obtained by vacuum induction levitation melting. The vacuum degree of vacuum induction levitation melting is controlled at 2×10 -3 Pa, the number of smelting times is controlled at 3 times, and the ingot with the size of Φ40×600mm is cast;
[0157] S2, casting: after removing the surface oxide scale of the ingot of S1 of the required quality, put it into a centrifugal casting machine, and cast it by the centrifugal casting machine. During the centrifugal casting process, asbestos is wrapped outside the casting mold to prevent cracks caused by rapid cooling. After the centrifugal casting is completed, the furnace temperature is lowered to 200°C and the mold is taken out of the furnace. When the shell temperature is lowered to below 100°C, the ceramic shell is removed by sandblasting, and the electrode rod is cut by wire cutting to obtain an electrode rod with a diameter of 40 mm;
[0158] S3, surface treatment and processing: remove the surface oxide scale and chamfer the electrode rod of S2, the surface roughness Ra = 2.0μm, the chamfer radius size is R3.5mm, and then chamfer the corners to obtain an electrode rod with a diameter of 35mm suitable for the rotating electrode method;
[0159] S4, alloy powder preparation: the electrode rod of S3 is used to prepare alloy powder by a rotating electrode method, and the protective atmosphere used in the rotating electrode preparation of the alloy powder is high-purity argon gas to obtain alloy powder for 3D printing. The particle size of the alloy powder for 3D printing is 55-125 μm and the oxygen content is 350 ppm;
[0160] S5. Alloy powder processing: The alloy powder for 3D printing of S4 is screened and packaged. When packaging the alloy powder, the container needs to be filled with argon and then sealed to obtain a finished alloy powder for 3D printing with a powder particle size of 45-150μm and an oxygen content of less than 500ppm; the fluidity of the alloy powder for 3D printing should be less than 30s / 50g, the hollow powder rate should be less than 0.1%, and the bulk density should be greater than 2.4g / cm 3 , tap density greater than 2.5g / cm 3 ;
[0161] S6, electron beam selective melting: Before the finished alloy powder for 3D printing of S5 is subjected to electron beam selective melting printing, it is necessary to use a PRS device to screen it once, and then the screened finished alloy powder for 3D printing is spread on the powder for electron beam selective melting printing. A layer thickness of 50 μm is selected during the powder spreading process. During the electron beam selective melting process, the target temperature of the powder bed sintering process reaches 1190°C, and the temperature reaches the Tα value as much as possible within the working range of the machine to prepare a gradient structure TiAl alloy blade;
[0162] In S6, the base plate needs to be preheated before powder coating in electron beam selective melting printing, and the preheating temperature reaches 1220℃ and the preheating time is 30min; the preheating adopts 5+5+10 electron beam scanning, and the current gradually increases from 12 to 20 in the first 5 times, from 20 to 40 in the middle 5 times, and from 40 to 60 in the last 10 times; the melting parameters of the lower equiaxed crystal part in electron beam selective melting printing use a current of 8.5mA, a scanning speed of 2.0m / s, a random point melting mode is selected for the scanning path, and the defocus value is 30; the melting parameters of the upper columnar crystal part in electron beam selective melting printing use a current of 7.5mA, a scanning speed of 1.8m / s, a line-scan mode is selected for the scanning path, and the defocus value is 30; the melting parameters of the transition zone in electron beam selective melting printing use automatic interpolation method, and the transition layer is not less than 10 layers when the layer thickness is 50μm, and the transition layer is not less than 8 layers when the layer thickness is 70μm.
[0163] In this embodiment, the gradient structure TiAl alloy blade prepared is anatomically analyzed. The tenon part should be entirely equiaxed crystals, and the blade body part should be entirely columnar crystals.
[0164] The tenon head of the gradient structure TiAl alloy blade prepared in this embodiment is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystal, and the columnar crystal part is α 2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0165] The average grain size of the equiaxed crystals in the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment is 6 μm, and the average grain size of the columnar crystals in the blade body part is 40 μm.
[0166] The room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade prepared in this embodiment are as follows: tensile strength of 600 MPa, yield strength of 520 MPa, yield strength ratio of 0.867, elongation of 2.5%, strength-plastic product of 1.50 GPa·%, and fatigue limit of 510 MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength of 780 MPa, yield strength of 640 MPa, yield strength ratio of 0.821, elongation of 1.2%, strength-plastic product of 0.94 GPa·%, and fatigue limit of 590 MPa.
[0167] The above scheme, the present invention proposes a gradient structure TiAl alloy blade and a preparation method, which can solve many technical problems existing in the preparation process of TiAl alloy blades, thereby reducing production costs and improving economic benefits.
[0168] The present invention prepares alloy powder through the preparation and reasonable parameter adjustment, utilizes the relationship between energy input-electron beam morphology-crystal growth, uses electron beam selective melting of alloy powder to prepare, realizes the gradient structure of lower equiaxed crystal-upper columnar crystal by controlling the energy input density and electron beam morphology, realizes the crack-free transition interface in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method; the structure can utilize the unique mechanical properties of different microstructures to match the service requirements of different parts of the blade, and proposes a new concept for the material-function integration of 3D printed TiAl blades.
[0169] The preparation of the alloy powder of the present invention requires controllable composition design, and the electrode rod is obtained by two castings. The electrode rod can only be obtained by the rotating electrode method. The prepared alloy powder for electron beam selective melting should have a fluidity of less than 30s / 50g, a hollow powder rate of less than 0.1%, and a loose density of more than 2.4g / cm 3 , tap density greater than 2.5g / cm 3 .
[0170] The base plate needs to be preheated before the powder is spread by electron beam selective melting printing of the present invention. The preheating adopts 5+5+10 electron beam scannings. The current is gradually increased from 12 to 20 in the first 5 times, from 20 to 40 in the middle 5 times, and from 40 to 60 in the last 10 times, so that the base plate is preheated to a sufficient temperature without deformation.
[0171] Reasonable parameter adjustment of the present invention includes current, scanning speed, and defocus value, so that two different microstructures can be printed on a blade without increasing printing steps and links, thereby realizing structural and functional integration.
[0172] The hot isostatic pressing treatment of the present invention can eliminate defects occurring during the printing process of the prepared TiAl alloy blade and effectively improve the mechanical properties.
[0173] The heat treatment after hot isostatic pressing of the present invention can enable the prepared TiAl alloy blade to obtain an optimized microstructure with the characteristics of fine full lamellar layers.
[0174] The tenon of the gradient structure TiAl alloy blade prepared by the present invention is divided into equiaxed crystals, and the equiaxed crystal part is α 2 +β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystal, and the columnar crystal part is α 2 +γ two-phase microstructure, a crack-free transition interface was achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
[0175] The room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade prepared by the present invention are as follows: tensile strength of 600-700 MPa, yield strength of 500-600 MPa, yield strength ratio of 0.823-0.929, elongation of 2-3%, and fatigue limit of 500-600 MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength of 700-900 MPa, yield strength of 600-800 MPa, yield strength ratio of 0.821-0.900, elongation of 0.5-1.5%, and fatigue limit of 500-700 MPa.
[0176] In summary, compared with other traditional methods, the method of the present invention prepares and adjusts the tenon and blade body of the blade with different organizational structures through the selection and preparation of the composition of the alloy powder and the regulation of the electron beam selective melting process steps; it can simultaneously meet the room temperature and high temperature performance requirements of the tenon and blade body of aviation alloy blades, has high resource utilization, short process, high efficiency, and is conducive to large-scale industrial production and promotion.
[0177] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.
[0178] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.
[0179] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0180] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A gradient structure TiAl alloy blade, characterized in that: The gradient structure TiAl alloy blade has a length of 70-300 mm, a thickness of 3-15 mm, and a chemical composition by mass percentage of: Al 40-49 at%, Nb 4-8 at%, Mo 0.2-0.9 at%, Si 0-0.2 at%, B 0-0.2 at%, C 0-0.2 at%, and the remainder is Ti and unavoidable inclusions; wherein the lower limits of the aforementioned elements Si and B cannot be 0.
2. The gradient structure TiAl alloy blade according to claim 1, characterized in that: The tenon part of the gradient structure TiAl alloy blade is divided into equiaxed crystals, and the equiaxed crystal part is an α2+β+γ three-phase microstructure; the blade body part of the gradient structure TiAl alloy blade is columnar crystals, and the columnar crystal part is an α2+γ two-phase microstructure, and a crack-free transition interface is achieved in the equiaxed crystal-columnar crystal transition zone by automatic interpolation method.
3. The gradient structure TiAl alloy blade according to claim 2, characterized in that: The room temperature mechanical properties of the tenon part of the gradient structure TiAl alloy blade are as follows: tensile strength of 600-700MPa, yield strength of 500-600MPa, yield strength ratio of 0.823-0.929, elongation of 2-3%, and fatigue limit of 500-600MPa; the room temperature mechanical properties of the blade body part are as follows: tensile strength of 700-900MPa, yield strength of 600-800MPa, yield strength ratio of 0.821-0.900, elongation of 0.5-1.5%, and fatigue limit of 500-700MPa.
4. A method for preparing a gradient structure TiAl alloy blade according to claim 1, characterized in that: The preparation method of the gradient structure TiAl alloy blade comprises the following steps: S1. Melting: weighing and mixing pure metal Ti and Al with a purity of 99.9% and master alloys Al-Nb, Al-Mo and Al-Si as raw materials according to the composition ratio, using vacuum induction suspension melting to obtain alloy melt, and casting to obtain ingots; S2, casting: casting the ingot of S1 of required mass by a centrifugal casting machine to obtain an electrode rod; S3, surface treatment and processing: remove the surface oxide scale of the electrode rod of S2, and then round off the corners to obtain an electrode rod suitable for the rotating electrode method; S4, alloy powder preparation: the electrode rod of S3 is used to prepare alloy powder by a rotating electrode method to obtain alloy powder for 3D printing; S5, alloy powder processing: sieving and packaging the alloy powder for 3D printing in S4 to obtain finished alloy powder for 3D printing with a powder particle size controlled at 45-150 μm and an oxygen content controlled at less than 500 ppm; S6, electron beam selective melting: The finished alloy powder for 3D printing in S5 is subjected to electron beam selective melting printing to prepare a gradient structure TiAl alloy blade.
5. The method for preparing a gradient structure TiAl alloy blade according to claim 4, characterized in that: In S6, powder needs to be spread before electron beam selective melting printing. During the powder spreading process, a layer thickness of 50-100μm is selected. During the electron beam selective melting process, the target temperature of the powder bed sintering process reaches 1170-1190℃.
6. The method for preparing a gradient structure TiAl alloy blade according to claim 4, characterized in that: In S6, the melting parameters of the lower equiaxed crystal part in the electron beam selective melting printing use a current of 8-8.5mA, a scanning speed of 1.9-2.1m / s, and a defocus value of 30-50; the melting parameters of the upper equiaxed crystal part in the electron beam selective melting printing use a current of 7.5-8mA, a scanning speed of 1.8-2.0m / s, and a defocus value of 30-35.
7. The method for preparing a gradient structure TiAl alloy blade according to claim 4, characterized in that: In S6, the transition zone melting parameters in electron beam selective melting printing use automatic interpolation method. When the layer thickness is 50μm, the transition layer is not less than 10 layers, and when the layer thickness is 70μm, the transition layer is not less than 8 layers. The post-preheating parameters in electron beam selective melting printing use an average beam current of 12 and perform 15 scans.
8. The method for preparing the gradient structure TiAl alloy blade according to claim 4, characterized in that: After the electron beam selective melting printing in S6 is completed, the printed product needs to be subjected to hot isostatic pressing. The process parameter temperature should not be higher than 1240°C and the pressure should be higher than 200MPa. After the hot isostatic pressing is completed, the printed product needs to be heat treated. The heat treatment parameter temperature should not be higher than 1275°C and the time should not be higher than 10 minutes.
9. The method for preparing a gradient structure TiAl alloy blade according to claim 4, characterized in that: CT analysis of the alloy blades after heat treatment should show no holes at a scanning accuracy of 30μm.
Citation Information
Patent Citations
Preparing method of TiAl alloy turbine blade
CN107931609A
Method for manufacturing tial alloy impeller, and tial alloy impeller
CN112996993A
Method for preparing deformed TiAl alloy blade
CN116393928A
Preparation method of gradient strategy 3D printing TiAl alloy
CN116851772A
Deformed high Nb-TiAl alloy with fine similar gamma tissue structure and preparation method of deformed high Nb-TiAl alloy
CN117026007A
